تطوير محطة الكتروكيميائية أوتوماتيكية لقياس الأوزون و مؤكسدات الهواء الأخرى بالنمط المتقطع والمستمر - ماضي راشد, جبار; عجيل عبيد, كاظم; محمد جلود, موفق (University of Thi-Qar Journal of Science, 2011)
An automatic electrochemical system developed to monitor ozone concentration in air .The principal feature for this system its working according to the principle of chemical illuminants which generates from the surface reaction of ozone gas with hydroxide solution 5- amino methylene hydrozide . All parts of our system assembled, manufactured , tested and calibrated in our labs. Using OL80/DLS ozone calibrator. The tested results show that the sensitivity of detection of ozone gas approximates and extends to less-than-nanogram.